2008
DOI: 10.1111/j.1467-7652.2008.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulated expression of plant‐specific glycoepitopes in alfalfa

Abstract: Summary Compared with other plant expression systems used for pharmaceutical protein production, alfalfa offers the advantage of very homogeneous N‐glycosylation. Therefore, this plant was selected for further attempts at glycoengineering. Two main approaches were developed in order to humanize N‐glycosylation in alfalfa. The first was a knock‐down of two plant‐specific N‐glycan maturation enzymes, β1,2‐xylosyltransferase and α1,3‐fucosyltransferases, using sense, antisense and RNA interference strategies. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 77 publications
0
64
0
Order By: Relevance
“…Furthermore, plant glycoproteins contain paucimannosidic glycans, produced by the action of vacuolar or extracellular exoglycosidases, as well as a small proportion of Lewis a structures, caused by the addition of ␤1,3-linked galactose and ␣1,4-linked fucose to the terminal GlcNAc, which is thought to happen in the trans-golgi network (Saint-Jore-Dupas et al, 2006). Plant N-linked glycosylation has been remodeled using two main approaches: reducing or eliminating endogenous enzymatic activities of ␤1,2-xylosyltransferase (␤1,2-XylT) and ␣1,3-fucosyltransferase (␣1,3-FucT) activities in the plant glycosylation pathway or introducing new recombinant enzymatic activities such as ␤1,4-galactosyltransferase or ␤1,4-Nacetylglucosaminyltransferase III (GnTIII) activities into the cells (Bakker et al, 2001;Cox et al, 2006;Koprivova et al, 2004;Palacpac et al, 1999;Rouwendal et al, 2007;Sourrouille et al, 2008;Strasser et al, 2004Strasser et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, plant glycoproteins contain paucimannosidic glycans, produced by the action of vacuolar or extracellular exoglycosidases, as well as a small proportion of Lewis a structures, caused by the addition of ␤1,3-linked galactose and ␣1,4-linked fucose to the terminal GlcNAc, which is thought to happen in the trans-golgi network (Saint-Jore-Dupas et al, 2006). Plant N-linked glycosylation has been remodeled using two main approaches: reducing or eliminating endogenous enzymatic activities of ␤1,2-xylosyltransferase (␤1,2-XylT) and ␣1,3-fucosyltransferase (␣1,3-FucT) activities in the plant glycosylation pathway or introducing new recombinant enzymatic activities such as ␤1,4-galactosyltransferase or ␤1,4-Nacetylglucosaminyltransferase III (GnTIII) activities into the cells (Bakker et al, 2001;Cox et al, 2006;Koprivova et al, 2004;Palacpac et al, 1999;Rouwendal et al, 2007;Sourrouille et al, 2008;Strasser et al, 2004Strasser et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…However, given the presence of gene families in plants, combined with the fact that homologous recombination in plants is very rare, the implementation of these approaches to other plant species is very difficult. As an alternative, gene silencing by RNAi of xylosyl-and fucosyltranferases has been established in several plant species, including Nicotiana benthamiana [33], Medicago sativa [34] and Lemna minor [35]. Through yet another approach, the addition of xylose and fucose was strongly inhibited in Nicotiana tabacum [36] via the expression of mutant galactosyltransferases, which appear to result in intermediate galactosylated N-glycan structures that are not the substrates for the xylosyl-and fucosyltransferases (Figure 1, Structure 9).…”
Section: Glycoengineeringmentioning
confidence: 99%
“…plants of A. thaliana were viable and exhibited no obvious phenotype under standard growth conditions (Strasser et al, 2004). In addition, the transgenic plants (L. minor, N. benthamiana, and M. sativa), in which Xyl and Fuc residues were eliminated by RNAi, did not exhibit any obvious morphological phenotype (Cox et al, 2006;Sourrouille et al, 2008;Strasser et al, 2008). In our study, we also found that the deficiency of XylT and FucT did not affect the morphology, growth rate, or growth status of tobacco BY2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the glycan-optimized mAb exhibited high effector activities as compared to its Chinese hamster ovary (CHO)-derived homologs. Recently, several studies also showed that RNAi effectively prevented the function of β1,2-XylT and core α1,3-FucT in the whole plant of N. benthamiana and alfalfa, respectively (Sourrouille et al, 2008;Strasser et al, 2008). As compared to the whole plant, tobacco BY2 cells possess the merits of precise control over growth conditions, easy downstream processing, and no pollen contamination (Hellwig et al, 2004).…”
Section: Discussionmentioning
confidence: 99%